Economic and sociological aspects of the development of social entrepreneurship. (Journal of Economic Research & Business Administration, 2015)
This article deals with the problems of formation and development of socio-economic aspects of entrepreneurship in the global space. Consideration of the subject of his research methodological framework and practical mechanisms, identifies development factors based on the concepts of economic and sociological theories.